Dynamics of Inorganic Nutrients in Intertidal Sediments: Porewater, Exchangeable, and Intracellular Pools - Garcia-Robledo, Emilio; Bohorquez, Julio; Corzo, Alfonso; Jimenez-Arias, Juan L.; Papaspyrou, Sokratis (Frontiers in Microbiology, 2016)
The study of inorganic nutrients dynamics in shallow sediments usually focuses on two main pools: the porewater (PW) nutrients and the exchangeable (EX) ammonium and phosphate. Recently, it has been found that microphytobenthos (MPB) and other microorganisms can accumulate large amounts of nutrients intracellularly (IC), highlighting the biogeochemical importance of this nutrient pool. Storing nutrients could support the growth of autotrophs when nutrients are not available, and could also provide alternative electron acceptors for dissimilatory processes such as nitrate reduction. Here, we studied the magnitude and relative importance of these three nutrient pools (PW, IC and EX) and their relation to chlorophylls (used as a proxy for MPB abundance) and organic matter (OM) contents in an intertidal mudflat of Cadiz Bay (Spain). MPB was localized in the first 4 mm of the sediment and showed a clear seasonal pattern; highest chlorophylls content was found during autumn and lowest during spring-summer. The temporal and spatial distribution of nutrients pools and MPB were largely correlated. Ammonium was higher in the IC and EX fractions, representing on average 59 and 37% of the total ammonium pool, respectively. Similarly, phosphate in the IC and EX fractions accounted on average for 40 and 31% of the total phosphate pool, respectively. Nitrate in the PW was low, suggesting low nitrification activity and rapid consumption. Nitrate accumulated in the IC pool during periods of moderate MPB abundance, being up to 66% of the total nitrate pool, whereas it decreased when chlorophyll concentration peaked likely due to a high nitrogen demand. EX-Nitrate accounted for the largest fraction of total sediment nitrate, 66% on average. The distribution of EX-Nitrate was significantly correlated with chlorophyll and OM, which probably indicates a relation of this pool to an increased availability of sites for ionic adsorption. This EX-Nitrate pool could represent an alternative nitrate source with significant concentrations available to the microbial community, deeper in the sediment below the oxic layer.